Changes in lactate dehydrogenase are associated with central gray matter lesions in newborns with hypoxic-ischemic encephalopathy. (19th May 2017) - Yum, Sook Kyung; Moon, Cheong-Jun; Youn, Young-Ah; Sung, In Kyung
Abstract: Purpose : Biomarkers may predict neurological prognosis in infants with hypoxic-ischemic encephalopathy (HIE). We evaluated the relationship between serum lactate dehydrogenase (LDH) and brain magnetic resonance imaging (MRI), which predicts neurodevelopmental outcomes, in order to assess whether LDH levels are similarly predictive. Materials and methods : Medical records were reviewed for infants with HIE and LDH levels were assessed on the first (LDH1 ) and third (LDH3 ) days following birth. Receiver operating characteristic curves were obtained in relation to central gray matter hypoxic-ischemic lesions. Results : Of 92 patients, 52 (56.5%) had hypoxic-ischemic lesions on brain MRI, and 21 of these infants (40.4%) had central gray matter lesions. LDH1 and LDH3 did not differ; however, the percentage change (ΔLDH%) was significantly higher in infants with central gray matter lesions (36.9% versus 6.6%, p = 0.006). With cutoffs of 187 (IU/L, ΔLDH) and 19.4 (%, ΔLDH%), the sensitivity, specificity, positive predictive value and negative predictive value were 71.4, 69.0, 40.5 and 89.1%, respectively. The relative risk was 5.57 ( p = 0.001). Conclusion : Changes in serum LDH may be a useful biomarker for predicting future neurodevelopmental prognosis in infants with HIE.